CuFeS2 Nanoassemblies With Intense Near-Infrared Absorbance for Photothermal Therapy of Tumors - Huang, Shan; Li, Gang; Yang, Zhengyuan; Hua, Min; Yuan, Zhe; Jin, Xin (Frontiers in Materials, 2020)
Photothermal therapy is an efficient cancer treatment method. The development of nanoagents with high biocompatibility and near-infrared (NIR) photoabsorption band is a prerequisite to the success of this method. However, the therapeutic efficiency of photothermal therapy is rather limited because most of the nanoagents have a low photothermal conversion efficiency. In this study, we aimed to develop CuFeS2 nanoassemblies with an excellent photothermal effect using the liquid-solid-solution method. The CuFeS2 nanoassemblies we developed are composed of ultrasmall CuFeS2 nanoparticles with an average size of 5 nm, which have strong NIR photoabsorption. Under NIR laser illumination at 808 nm at the output power intensity of 1.0 W cm-2, the CuFeS2 nanoassemblies could rapidly convert NIR light into heat, achieving a high photothermal conversion efficiency of 46.8%. When K7M2 cells were incubated with the CuFeS2 nanoassemblies and then exposed to irradiation, their viability decreased progressively as the concentration of the CuFeS2 nanoassemblies increased. Furthermore, a concentration of 40 ppm of CuFeS2 nanoassemblies was lethal to the cells. Importantly, after intratumoral injection of 40 ppm CuFeS2 nanoassemblies, the tumor showed a high contrast in the thermal image after laser irradiation, and tumor cells with condensed nuclei and a loss of cell morphology could be thermally ablated. Therefore, the CuFeS2 nanoassemblies we synthesized have a high biocompatibility and robust photothermal effect and can, thus, be utilized as a novel and efficient photothermal agent for tumor therapy.